Effect of Giving Frass Hermetia Illucen L. on Soil Physical Chemical Properties, Chlorophyll Content and Yield of Upland Rice (Oryza Sativa L.) on Ultisol Soil - Reswita Reswita; Zozy Aneloi Noli; Resti Rahayu (Green Publisher Indonesia, 2022)
Ultisol soils i s a kind that experiences problems due to high acidity and Al saturation, low nutrient, and organic matter content, and are sensitive to erosion. Therefore, alternative efforts need to be made to overcome this, one of which is using Frass fertilizer from Black Soldier Fly fly larvae. Frass is the result of bioconversion as a by-product of rearing BSF larvae which contains a large number of nutrients that are useful for plants and also to overcome the problem of Ultisol soil. The purpose of this research knowing the effect of giving BSF Frass and the extent to which Frass fertilizer can replace the need for NPK fertilizer for upland rice (Oryza sativa L.) on Ultisol soil. The experiment was arranged in a factorial completely randomized design consisting of 2 factors and 3 replications Factor A as the total dose; control, 10% Frass, 20%, and 30% Frass, and Factor B as the dose of NPK fertilizer: 100% positive control (according to recommendations), 75%, 50%, and 25%. The results showed that the application of Frass can improve the physical and chemical properties of Ultisol soil, and increase the grain weight of 100 seeds. The combination of giving Frass 30% with 25% NPK had a significant effect on increasing the total chlorophyll content of upland rice leaves when compared to giving Frass with doses of 20% and 10% with all combinations of NPK. However, it was not significantly different when compared to the control combination which received treatment with NPK as much as 100% and 75%.It was concluded that the application of 30% Frass combined with 25% NPK fertilizer had a significant effect on the chlorophyll content of upland rice and had the potential to reduce the use of chemical fertilizers by 25%.